Bone morphogenetic proteins in tissue engineering: the road from laboratory to clinic, part II (BMP delivery) - Bessa, Paulo C. (2008)
Bone morphogenetic proteins (BMPs) are cytokines with a strong effect on bone and cartilage growth and with important roles during embryonic patterning and early skeletal formation. BMPs have promising potential for clinical bone and cartilage repair, working as powerful boneinducing components in diverse tissue-engineering products. Synthetic polymers, natural origin polymers, inorganic materials and composites may be used as carriers for the delivery of BMPs. Carriers range from nanoparticles to complex three-dimensional (3D) scaffolds, membranes for tissue-guided regeneration, biomimetic surfaces and smart thermosensitive hydrogels. Current clinical uses include spinal fusion, healing of long bone defects and craniofacial and periodontal applications, amongst others. BMP-2 and BMP-7 have recently received approval by the US Food and Drug Administration (FDA) for specific clinical cases, delivered in absorbable collagen sponges. Considering the expanding number of publications in the field of BMPs, there are prospects of a brilliant future in the field of regenerative medicine of bone and cartilage with the use of BMPs.